Dream capitalism - Pierson, Christopher (Springer, 2015)
John Tomasi’s Free Market Fairness represents an heroic attempt to bridge the gap between Rawlsian ‘high liberals’ and the advocates of classical liberalism/contemporary libertarianism. I argue that Tomasi’s project fails, above all because it cannot give a compelling account of contemporary (American) capitalism or of its capacity to deliver free market fairness.